2016
DOI: 10.1163/15700666-12340073
|View full text |Cite
|
Sign up to set email alerts
|

From Swagger to Serious: Managing Young Masculinities between Faiths at a Young Men’s Christian Association Centre in The Gambia

Abstract: A renewed focus on studies of masculinity in Africa has so far failed to account for the growing importance of nonproselytizing Faith-Based Organisations (fbos) in the gendering process. This article seeks to address this issue through a case study of the Gambian branch of the Young Men’s Christian Association (ymca).ymcaleaders generate a culture of dynamic leadership that equates to a form of ‘hegemonic masculinity’ based on love, self-sacrifice, and obligation. This article shows how this process is implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This leads to polarised narratives of youth and masculinity centred on either being productive economic actors or destructive political actors, with little room in between for ambiguity, nuance or lived realities (Wignall 2016). In the Gambian context, categories of manhood are dictated by The Gambia's paradoxical recent history as a self-styled Islamic state and a hedonistic tourist destination (see Wignall 2017). In the midst of these intersecting global and local forces, young men experience exclusion and marginalisation through both febrile and exclusive ethnic5 and governance structures and from the older generations who see youth as a threat (Janson, 2013).…”
Section: Marginal Masculinities In the Neoliberal Landscapementioning
confidence: 99%
See 3 more Smart Citations
“…This leads to polarised narratives of youth and masculinity centred on either being productive economic actors or destructive political actors, with little room in between for ambiguity, nuance or lived realities (Wignall 2016). In the Gambian context, categories of manhood are dictated by The Gambia's paradoxical recent history as a self-styled Islamic state and a hedonistic tourist destination (see Wignall 2017). In the midst of these intersecting global and local forces, young men experience exclusion and marginalisation through both febrile and exclusive ethnic5 and governance structures and from the older generations who see youth as a threat (Janson, 2013).…”
Section: Marginal Masculinities In the Neoliberal Landscapementioning
confidence: 99%
“…Coupled with the difficulties of finding a sustainable livelihood due to the unbalanced Gambian economy, young men often feel multiply marginalised and access NGOs both as routes to local empowerment and as portals to another realm, both real and imagined, of global opportunity. However, it is important to note that, like young working-class boys in the UK, young Gambian men are also exerting their agency in innovative ways, and many of the young men I worked with were using the Sports Leadership course as a stepping stone to coaching careers, community work or even teaching (see Wignall, 2017). With this ambiguity in mind, in the following sections I explore these tensions through a series of ethnographic moments and portraits of young men in the Sports (Fieldnotes, 16th April 2011) This vignette demonstrates the delicate and often problematic process of trying to transform the young men who join the course.…”
Section: Marginal Masculinities In the Neoliberal Landscapementioning
confidence: 99%
See 2 more Smart Citations
“…Jones (2009; has suggested that to understand what creates meaningful social belonging and societal change in rural Africa, one should look beyond the state, while Englund (2011a), has suggested replacing sterile debates about the content and definition of 'politics' with analysis of how adherents draw on religion in their everyday lives, including in their political actions and thoughts. In this vein, Ross Wignall's work has interpreted religion in Africa through a focus on how faith-based organizations seek to mould moral subjectivities and, in so doing, entrench neoliberal subjectivity among the targets of their youth work (Wignall 2016). In the case I present, as in the case described by Wignall, religion is not solely an arena for religious expression, but provides a space and platform from which young people can question the authority of their elders, and advance critiques of the ill-functioning politics of the state.…”
Section: Unpacking Politics and Religionmentioning
confidence: 99%